Characterization of basic immune function parameters in the fathead minnow (Pimephales promelas), a common model in environmental toxicity testing. Issue 61 (February 2017) - Thornton, Leah M.; LeSueur, Meriel C.; Yost, Alexandra T.; Stephens, Dane A.; Oris, James T.; Sellin Jeffries, Marlo K.
Abstract: The fathead minnow ( Pimephales promelas ) is an environmental sentinel species, commonly used in toxicity testing. However, there is a lack of data regarding basic immune function in this species. To improve the usefulness of the fathead minnow as a model for basic immune function and immunotoxicity, this study sought to 1) compare the differential expression of immune function genes in naïve fathead minnows and 2) determine the effects of pathogen exposure on immune gene expression and spleen index. To accomplish this, kidney, spleen and liver tissue were collected three days post injection (dpi) from adult male fathead minnows from each of the following groups: 1) uninjected control 2) sham-injected (Hank's balanced salt solution) and 3) pathogen-injected ( Yersinia ruckeri ). Spleen tissue was also collected at seven and 14 dpi. Differential tissue expression of immune function genes was evaluated in naïve minnows and expression patterns were similar to those found in other fish species, with liver tissue generally having the highest amount of expression. Following pathogen injection, the expression of complement component 3 ( c3 ) (4.4-fold, kidney; 2.5-fold, liver), interleukin 11 ( il11 ) (4.8-fold, kidney; 15.2-fold, liver) and interleukin 1β ( il1β ) (8.2-fold, kidney; 17.2-fold, spleen; 2.6-fold, liver) were significantly upregulated. Elastase 2 ( elas2 ) was significantly downregulated (5.8-fold) in liver tissue. A significant increase in spleen index at seven dpi was also observed in pathogen-injected minnows. This study has identified endpoints that are part of the normal response to pathogen in fathead minnows, an essential step toward the development of the fathead minnow as a model for immunotoxicity evaluations. Highlights: Hepatic tissue had the highest expression of immune-related genes in naïve fish. Pathogen injection resulted in alterations in expression of immune-related genes. Spleen index was significantly increased seven days following pathogen injection. Immune-sensitive endpoints can be utilized in future studies using this species.